Neutron‐activatable needles for radionuclide therapy of solid tumors. Issue 12 (15th September 2017) - Kim, Junghyun; Narayan, Roger J.; Lu, Xiuling; Jay, Michael
Abstract: Various approaches have been undertaken to enhance the delivery of therapeutic agents, including tissue‐killing radionuclides, into solid tumors. Here, we describe the preparation of conical needles composed of Ti and Mo coated by pulsed laser deposition or chemical vapor deposition with elements (Ho and Re) that can readily yield radioactive isotopes following irradiation in a neutron flux. The radioactive needles, whose design were based on solid microneedle arrays used in transdermal drug delivery, can be produced with minimal handling of radioactivity and subsequently inserted into tumors as a means of internal radiation therapy. Ho and Re were specifically chosen because of their large neutron capture cross‐sections as well as the desirable radiotherapeutic properties of the resultant radionuclides. Neutron‐absorbing shields were also developed to prevent the production of unwanted radionuclides after neutron irradiation of the needle base materials. Neutron activation calculations showed that therapeutically significant amounts of radionuclides can be produced for treating solid tumors. Stability studies demonstrated that Re did not leach off the Mo needles. These coated neutron‐activatable needles offer a new approach to internal radiation therapy of tumors that allows precise tailoring of the absorbed radiation dose delivered to the tumor by controlling the coating thickness and the irradiation time. © 2017 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 105A: 3273–3280, 2017.